PERSEPSI PASIEN BPJS KESEHATAN TERHADAP PELAYANAN RAWAT JALAN DI UPTD PUSKESMAS HARAPAN RAYA PEKANBARU - Frimusdya, Tirza; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Health services that are less than optimal are the most common constraints felt by the people today, especially in first-level health facility services. One of the first level health facilities namely public health centers. This needs to be improved because of the many complaints from patients about the outpatient services they undergo, especially in patients who use health cards (BPJS kesehatan). This study aims to determine the forms of outpatient services available at the public health center and to find out the perceptions of BPJS outpatient patients on the services provided by the Harapan Raya Pekanbaru Public Health Center. This study uses descriptive quantitative methods. The population in this study were all patients using BPJS kesehatan services who were used outpatient treatment at Harapan Raya Public Health Center in the last month of patient visits totaling 922 people. Sampling is done by simple random sampling technique with a total sample of 90 respondents. Data collection uses the method of observation, documentation and interviews. Based on the results of the study can be concluded that BPJS patients outpatient health service gave “not good enough” responses to the provided service by Harapan Raya Public Health Center. This could be seen from 5 service characteristics, there are 3 service characteristics that received negative responses, which are the level of service guarantees with the percentage is 50,0%, the level of service responsiveness of officers is 53,3% and the level of attention of service officers is 46,7%. Keywords: Perception, Patient, Service